HGG-17. NEW PHARMACOLOGICAL APPROACHES IN GLIOBLASTOMA THERAPY: BIOLOGICAL EFFECTS AND MOLECULAR ALTERATIONS. (23rd April 2019) - Iorio, Anna Lisa; Ros, Martina Da; Gregorio, Veronica De; Giunti, Laura; Genitori, Lorenzo; Sardi, Iacopo
Abstract: INTRODUCTION: Although decades of research have been trialed, the prognosis for patients with glioblastoma (GBM) has not significantly changed, highlighting the urgency of innovative strategies. Therefore, we investigated on GBM preclinical models the potential of a new pharmacological approach, combining doxorubicin (Dox), a historical anticancer agent with a high toxicity in vitro, and rapamycin (Rapa), a potent inhibitor of cell proliferation. METHODOLOGIES: We analyzed the synergistic effect obtained using Dox combined to Rapa on A172, U87MG and T98G GBM cell lines. MTT and TUNEL analysis were used to assess cytotoxicity and apoptosis. We also evaluated the effectiveness of the treatment in an orthotopic xenograft mice model of GBM with U87MG-luc cells by treatment with Dox, Rapa and their combination. At the end of experiments, brain tissues were collected for histological analysis. RESULTS: In vitro results showed that T98G was resistant to Dox but sensible to Rapa. Prolonging treatments, we observed a significant difference comparing Rapa vs Dox plus Rapa groups (p<0, 001), indicating that Rapa sensitizes T98G to Dox. In vivo results showed that Rapa and Dox determined a tumor growth inhibition from 86% to 97%; the most important action was given by Rapa plus high Dox treatment (-97%). However, this combination resulted in greater toxicity. It would be more appropriate to use Rapa plus lower Dox, which shows a tumor inhibition similar to Rapa plus high Dox with a lower toxicity. CONCLUSIONS: More studies are necessary to well understand the appropriate schedule of co-treatment but, this safe and non-invasive approach could be a successful strategy to increase the quality of life and survival rate of "poor-responder" brain tumor patients.